Unsteady shock wave dynamics - BRUCE, P. J. K.; BABINSKY, H. (Journal of fluid mechanics, 2008)
An experimental study of an oscillating normal shock wave subject to unsteady periodic forcing in a parallel-walled duct has been conducted. Measurements of the pressure rise across the shock have been taken and the dynamics of unsteady shock motion have been analysed from high-speed schlieren video (available with the online version of the paper). A simple analytical and computational study has also been completed. It was found that the shock motion caused by variations in back pressure can be predicted with a simple theoretical model. A non-dimensional relationship between the amplitude and frequency of shock motion in a diverging duct is outlined, based on the concept of a critical frequency relating the relative importance of geometry and disturbance frequency for shock dynamics. The effects of viscosity on the dynamics of unsteady shock motion were found to be small in the present study, but it is anticipated that the model will be less applicable in geometries where boundary layer separation is more severe. A movie is available with the online version of the paper.